(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
One of the most frequent acute purulent-inflammatory diseases of the middle ear in children is recurrent purulent otitis media. The main causes of the disease are premature birth, epidemics of acute respiratory infections among children, a tendency to family allergies, artificial nutrition, low immunity, negative factors of life and work, exudative diathesis, rickets, vitamin deficiency. The aim of our study was to study the features of the clinical course of recurrent purulent otitis media in children and the effectiveness of complex treatment. 21 children under the age of 5 were involved in the examination. All patients underwent a comprehensive clinical and laboratory examination. At the same time, all patients were consulted by a pediatrician and other necessary specialists. Microscopic examination of the smear from the ear revealed an increased content of aerobic microbes. It was found that 12 of the examined patients had acute rhinosinusitis, adenoids, 10 had acute respiratory diseases, zotiliam, acute bronchitis, exudative diathesis. In all examined patients, the otoscopic picture corresponds to the clinical picture of acute inflammation. The external auditory canal was cleaned daily from purulent secretions, a 0.05% solution of nasivin was instilled into the nasal cavity and washed with antiseptic solutions. A local antibiotic and antiseptic steroid mixtures were injected into the middle ear through the external auditory canal. All the sick children underwent physiotherapy procedures. Recurrent otitis media is a disease with complex pathogenetic factors that requires an integrated approach to treatment and diagnosis.